2015
DOI: 10.1017/s0950268815002174
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of severe diarrhoea due toVibrio choleraein the catchment area of six surveillance hospitals in Bangladesh

Abstract: SUMMARY Cholera is an important public health problem in Bangladesh. Interventions to prevent cholera depend on their cost-effectiveness which in turn depends on cholera incidence. Hospital-based diarrhoeal disease surveillance has been ongoing in six Bangladeshi hospitals where a systematic proportion of patients admitted with diarrhoea were enrolled and tested for Vibrio cholerae. However, incidence calculation using only hospital data underestimates the real disease burden because many ill persons seek trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…At the district hospital during the intervention, there was one post-discharge death that occurred after the majority of the diarrheal symptoms had resolved (see hospital and post-discharge course). This event generated a case fatality rate (CFR) of 0.1% for the entire study (1 out of 954 total patients including patients in the onboarding periods) and 0.3% for the district intervention which are similar to expected CFRs at similar sites [ 17 , 19 ]. These preliminary data suggest that the Rehydration Calculator is a safe tool to improve guideline adherence for diarrheal disease decision-support.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…At the district hospital during the intervention, there was one post-discharge death that occurred after the majority of the diarrheal symptoms had resolved (see hospital and post-discharge course). This event generated a case fatality rate (CFR) of 0.1% for the entire study (1 out of 954 total patients including patients in the onboarding periods) and 0.3% for the district intervention which are similar to expected CFRs at similar sites [ 17 , 19 ]. These preliminary data suggest that the Rehydration Calculator is a safe tool to improve guideline adherence for diarrheal disease decision-support.…”
Section: Discussionmentioning
confidence: 90%
“…The study consisted of a 6 week pre-intervention and 6 week intervention period; standard of care was maintained throughout the study except that the Rehydration Calculator was used by the admitting clinician during the intervention period only. The study was conducted from September to December 2015, when cholera outbreaks typically occur in northern Bangladesh [ 19 ]. The pre-intervention and intervention periods each spanned 36 study days from September 19 to November 5, 2015, and from November 15 to December 29, 2015, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A recent estimate based on a meta-analysis reported the incidence of rotavirus infections to be 100 cases per 1000 under-five children [21]. In contrast, a community-based study conducted in 2010-11 in the catchment area of six surveillance hospitals in Bangladesh estimated the incidence of severe diarrhoea due to cholera to range from 1 to 11 per 1000 among under-five children [22]. The Cholera Vaccine Investment Country Case Study in 2013 also reported a similar cholera incidence among under-five children, at a rate of about 8/1000 nationally and 11-12/1000 in the high risk districts [23].…”
Section: Resultsmentioning
confidence: 99%
“…Validation of this method is also required in each setting before using it as an alternative of the house-to-house survey. The estimates of jaundice-associated mortality obtained in this study can be used in conjunction with hospital-based diagnoses of hepatitis to calculate population-based estimates of cause-specific hepatitis mortality, including hepatitis E. [21][22][23] While the heaviest burden of hepatitis rests in low-and middle-income countries, 35 this low-cost survey method could be a valuable tool for estimating true global burden of hepatitis to track progress toward the WHO target of elimination of viral hepatitis by 2030. 7,9…”
Section: Discussionmentioning
confidence: 99%
“…21 We earlier took advantage of this strong community knowledge to identify patients with severe illness in the rural communities of Bangladesh. [21][22][23] In this study, we adapted this community knowledge approach to identify maternal and jaundiceassociated deaths in rural communities and estimated its sensitivity and cost savings compared with the house-tohouse survey approach.…”
Section: Introductionmentioning
confidence: 99%